Peripheral neuropathy in a case with CADASIL: a case report - Yusuke Sakiyama; Eiji Matsuura; Yoshimitsu Maki; Akiko Yoshimura; Masahiro Ando; Miwa Nomura; Kazuya Shinohara; Ryuji Saigo; Tomonori Nakamura; Akihiro Hashiguchi; Hiroshi Takashima (BMC Neurology, 2018)
Abstract Background Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is characterized clinically by central nervous system dysfunctions. It is unclear whether CADASIL is involved in peripheral neuropathy. Case presentation A 67-year-old Japanese man with stepwise progression of sensory and motor neuropathy was admitted to our hospital. Peripheral neuropathy of the extremities was detected through electrophysiological and pathological studies, and brain magnetic resonance imaging revealed bilateral periventricular ischemic and thalamic hemorrhagic lesions. We diagnosed CADASIL after detecting granular osmiophilic material in the walls of the endoneurial vessels morphologically and identifying a heterozygous NOTCH3 mutation p.Arg75Pro. Conclusions CADASIL is to be included in the work-up of not classified peripheral neuropathies.